An Analysis of Students’ Listening Skill through Podcast at Tenth Grade of SMK Negeri 6 Padang - Prinanda Tito Ramadhan; Elda Martha Suri; Yessy Marzona (JURNAL ARMADA PENDIDIKAN, 2026)
Podcast is an online media that provides content for listeners around the world. The purpose of this research was to determine the level of students listening skill and the difficulties for students in listening through podcast. The research that used descriptive method had a population of 134 people with Class X Fashion Design Department 2 that consisted of 33 students. The research instrument was a written test in 20 questions format and a podcast provided by the researcher in 30 minutes time period. This research used the rubric score that was adopted from Highline College Writing and score classification by Arikunto. This research also used 2 ways to analyze the data: mean and percentage. The results of the research stated that the average score of students in listening test was 67.67 and the lowest score in aspects of listening was to respond with 17.71%. In conclusion, all students in the class had a high level of listening and the most difficult aspect of listening for students to do was to respond.